Salt Eruptions and Their Role in the Shaping of the Oil Trapping for Selected Fields in Eastern Iraq - Razzaq, Harith A.; Al-kubaisi, Manal Sh; Muhsin, Suhail U. (Iraqi Journal of Science, 2023)
This research had been achieved using 2D seismic sections to study the presence of subsurface salty bodies in the Khashim Al-Ahmer, Galabat, Injana fields as a case study. The selected oil fields is located to the northeast of Baquba city within Diyala Governorate. The study aims to determine the salt accumulations of the selected fields and their role in the formation of oil traps. The interpretation of seismic data was focused on two reflectors Fatha and Jeribe Formations which belong to the lower and Middle Miocene. Structurally, Two systems of reversal faults are affecting the fields, according to seismic sections, the first represents thrust faults affected on the top part of Fatha (Red Beds & Seepage) and the layers above with large displacements and trending in an NW-SE orientation; The separation surface of these faults is the salt bed in the Fatha Formation. the second represents reversal faults affected on the lower section of Fatha (Transition beds) and the layers beneath with high displacements. The research concludes Petroleum flow from the source was directed by the faults created by the broad Zagros tectonism to Miocene and younger traps, also seal fracturing exceeds vertical petroleum flow. The differences in fault types are caused by the presence of a salt bed within the Fatha Formation and the high variation in its thickness at the crest and flanks. So, the main recommendation of research is to implement a 3D seismic survey covering these fields to determine salt body areas.